COMPARATIVE STUDY IN ANTIOXIDANT ACTIVITIES OF THE DIFFERENT RIPENESS STAGES OF ARTOCARPUS HETEROPHYLLUS LAM. FRUIT - Peramunugama, Dinushi; Chamara, Adikari Mudiyanselage Ruhunu; Thiripuranathar, *Gobika (International Journal of Ayurveda and Pharma Research, 2018)
The ethyl acetate extracts obtained from under-ripe (Young Stage), mature (Mature Stage) and ripe fruit (Ripe Stage) fruit pulp of Artocarpus heterophyllus Lam. were evaluated for their Total Phenolic Content, Total Flavonoid Content and antioxidant property. Total Moisture Content and the Total Ash Content of pulp were determined by subjecting to heat treatment. Total Phenolic Content was evaluated using Folin-Ciocalteu method and Total Flavonoid Content by Aluminium Chloride Colorimetric Assay. Antioxidant activity was determined by DPPH Radical Scavenging, ABTS Radical Scavenging and FRAP Assays. The highest moisture content varies as Young Stage>Mature Stage>Ripe Stage in 84.71% to 70.38% range and Total Ash Content of the Ripe Stage pulp was the highest (6.86 %) and the least was observed for the Young Stage with a value of 5.40 %. For the Total Phenolic Content, crude extracts isolated from Mature Stage showed highest value (434.04 mg GAE/g) and Total Flavonoid Content was highest in crude extract of the Young Stage (446.79 mg QE/g). Ripe Stage Crude extract gave lowest value for both Total Phenolic Content and Total Flavonoid Content. For DPPH Radical Scavenging, ABTS Radical Scavenging and FRAP Assays, highest activity was reported by crude extract of Young Stage followed by crude extract of Mature Stage and least activity was given by crude extract of Ripe Stage. A correlation between Total Phenolic Content and Total Flavonoid Content with antioxidant activity was noticeable. A declination of the antioxidant activity was observed as the fruit reaches its maturity.